2014
DOI: 10.1111/cxo.12119
|View full text |Cite
|
Sign up to set email alerts
|

Australian optometric and ophthalmologic referral pathways for people with age‐related macular degeneration, diabetic retinopathy and glaucoma

Abstract: Background: This study investigated the referral pathways offered to patients with agerelated macular degeneration (AMD), diabetic retinopathy (DR) or glaucoma (GL) by ophthalmologists and optometrists. Methods: Australian ophthalmologists and optometrists were surveyed regarding referral decisions to other eye-care specialists (inter-or intra-professional), general medical practitioners (GPs), low vision rehabilitation (LVR) and support services. Thematic analysis and concept mapping were applied to highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Many optometrists and ophthalmologists commented on the lack of effective AMD care coordination in the current health system. Eyecare professionals' descriptions of a unidirectional, ineffective model of AMD care aligns with previous research findings [36][37][38]. Previous research has suggested that the role of the optometrist in the ophthalmic care pathway often goes unrecognised, with optometrists seen differently from other healthcare professionals [39].…”
Section: Models Of Care: a Role For Amd Case Managers?supporting
confidence: 77%
“…Many optometrists and ophthalmologists commented on the lack of effective AMD care coordination in the current health system. Eyecare professionals' descriptions of a unidirectional, ineffective model of AMD care aligns with previous research findings [36][37][38]. Previous research has suggested that the role of the optometrist in the ophthalmic care pathway often goes unrecognised, with optometrists seen differently from other healthcare professionals [39].…”
Section: Models Of Care: a Role For Amd Case Managers?supporting
confidence: 77%
“…In some cases, referral to other suitable services can address conditions with intermediate levels of urgency and accommodate patient readiness and their capacity to travel or pay costs associated with referral whilst also preventing unnecessary burden on ophthalmology. Finally, current two‐tiered eye‐care systems have been criticised as ‘fragmented’ and inefficient . Robust, efficient and targeted referral pathways that better utilise all of the eye‐care professions in order to optimise long‐term patient outcomes in macular disease need to be developed…”
Section: Introductionmentioning
confidence: 99%
“…The conventional referral pathway for patients with pigmented lesions in many eye‐care systems starts with an assessment in primary care, followed by referral to a general ophthalmologist, and then onto a retinal specialist or ocular oncologist as required. However, specialist care may be overburdened by false positive referrals of benign lesions, and inter‐optometric referrals are uncommon . Chronic and/or well controlled conditions may not require ophthalmological management .…”
Section: Introductionmentioning
confidence: 99%